Numerical Modelling of Wind Turbine Blade to Evaluate Damage due to Impact Loads - Satti, Muhammad Haris (275842); Dr. Sehar Shakir (USPCAS-E, NUST,Islamabad, 2022)
TH-461
Keywords: MS Thesis; MS ESE Thesis